Clinical and Epidemiological Characteristics of Pandemic Influenza A/(H1N1) in Hospitalized Pediatric Patients at a University Hospital, Istanbul, Turkey - Torun, Selda Hancerli (J Trop Pediatr, 2011)
Background: The aim of this study was to describe the clinical and epidemiological characteristics of pandemic influenza in hospitalized children. Methods: A total of 114 patients with suspected H1N1 virus infection were hospitalized, and nasal swabs were sent to National Influenza Reference Laboratory for confirmation of pandemic influenza A (H1N1) virus infection by rRT–PCR assay. Results: Forty-six female and 68 male patients were included in the study. Age of the patients ranged from 40 days to 16 years. Clinical and/or radiological pneumonia were detected in 96% of all. Sixteen patients required mechanical ventilation due to hypoxemia. Previously healthy children required mechanical ventilation and oxygen therapy more than patients with chronic diseases. Elevated levels of CRP and LDH in patients with respiratory distress and patients who required mechanical ventilation were statistically significant. Conclusion: Our study showed that progress of pandemic influenza infection in previously healthy children is as severe as their counterparts with chronic underlying diseases.